PROCEDURAL ACTIONS PERFORMED IN THE COURSE OF DETAINING A PERSON IN CRIMINAL PROCEEDINGS - Uzbekova Dilshoda Tulkinovna (Modern American Journals, 2026)
The article analyzes procedural actions carried out during the detention of a person in criminal proceedings, focusing on the legislation of the Republic of Uzbekistan. The study examines the legal nature of detention, procedural guarantees at the moment of factual deprivation of liberty, and mechanisms of prosecutorial and judicial control. Using a comparative legal method, the experience of Germany and Kazakhstan is analyzed in order to identify legal instruments that may be implemented in the national criminal procedure. The author substantiates proposals aimed at strengthening safeguards of personal liberty and improving the effectiveness of procedural control.
Keywords: Detention, criminal procedure, procedural guarantees, right to liberty, judicial control, Uzbekistan.